Development of urban green space affects neighborhood community social interaction - Rasidi, Mohd. Hisyam (2012)
While Malaysia is heading for urbanization, urban green space degradation had occurred. Malaysia’s typical urban green space had shown the demotion of social interaction among urban residents. Hence, this research aimed to understand the designs of typical Malaysian green spaces which are believed to enhance community social interactions. Variables measured were the physical and natural characters of selected green spaces including activities, attractions and settings. The observation took place during representative of weekday, weekend and public holiday in those green spaces. The result suggested that diversity of subspaces including vegetation density, animal populations, undulating landforms and water bodies afford social interaction behavior.